Dibenzazepine Bridged Network Polymeric Phthalocyanines as Degradable Heterogeneous Photocatalysts - Ahmetali, Erem; Kocaarslan, Azra; Trouillet, Vanessa; Heissler, Stefan; Brase, Stefan (WILEY-V C H VERLAG GMBH, 2026)
Recyclability and energy efficiency are inevitable requirements in todays synthetic materials, as well as functional efficiency. Network polymeric phthalocyanines (NP-Pcs) are versatile molecular frameworks which widely utilized in energy and electron transfer demanding applications, but light hasnt played a role before in their design and degradation. Herein, we introduce photodynamic dibenzazepine moiety into NP-Pcs to obtain degradable heterogeneous photocatalysts (NP-ZnPc and NP-CoPc). Singlet oxygen generation efficiency of NP-ZnPc is found to be high, almost completely quenching the absorbance of diphenylisobenzofuran (DPBF) within 30 s upon red light (lambda = 630 nm) irradiation. Supplementary reactions show that NP-ZnPc has the capability to oxidize methylphenyl sulfide with 100% yield in 4 h reaction time. Subsequently, PET-RAFT polymerization of 2-hydroxyethyl methacrylate is successfully initiated by NP-ZnPc in the presence of a chain transfer agent upon red light (lambda = 647 nm) irradiation. The linearity in the increase in molecular weight (14,400-21,200 g/mol) and the decrease in monomer concentration (ln([M]0/[M]t = 0.6-3.4) demonstrate the living characteristic of PET-RAFT polymerization. Thanks to its heterogeneous nature, NP-ZnPc is readily recovered and reused after polymerization up to three consecutive cycles without significant loss of performance. Notably, complete degradation of NP-Pcs was achieved under 254 nm light irradiation.
Keywords: Dibenzazepine; Heterogeneous photocatalysts; Network polymeric phthalocyanine; Photodynamic covalent bond; VISIBLE-LIGHT; SUBSTITUTED PHTHALOCYANINES; ZINC PHTHALOCYANINE; METAL; CATALYSTS; Chemistry